EFFECT OF CEMENT INJECTION ON SHEAR STRENGTH OF JOINTED ROCK - Salia Zakri (NIM : 22116003), Rizto
In mining activity always find various kinds of problems, one of which is a problem of stability. In natural conditions, the stability of a rock mass will always be affected by the presence of joint and structure, where this condition will reduce the mass strength of the rock. Beside the jointed rock mass, the joint surface roughness also has an effect on the decrease in rock shear strength, therefore reinforcement in the rock needs to be done. One of the many methods of rock strengthening, is cement injection. The effectiveness of cement injection to increase rock strength, needs to be further investigated. In this study, the samples used are artificial samples with moldano tara type cast material, this material is used to simplify and speed up the printing process carried out with silicone rubber. Each sample has different roughness with JRC values 8-10, 12-14, 16-18, and 18-20. Then this samples are injected with cement in the fracture, with a ratio of cement: water 4W:5C and 3W:2C. Cement injection material is composed of PCC (Portland Compossite Cement) type cement and water without any other mixed material. After that, direct shear testing is carried out, so that changes in shear strength are indicated by changes in the cohesion value and internal friction angle. The results of this study state that for samples with JRC 8-10, the composition of 4W: 5C is most effective for increasing the cohesion value by 398% and the internal friction angle 3%, while for JRC 12-14,16-18, and 18-20 the most optimal composition is 3W:2C which can increase the cohesion value between 6% - 45%, while the internal friction angle value in the range of 21% -26%. While for applications in the rock mass, it is necessary to take into account the value of the Geological Strength Index (GSI), the effect of the GSI value will reduce the value of cohesion, and otherwise will increase the value of the internal friction angle in the rock mass.